2016
DOI: 10.1212/nxi.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a pathogenic role for CD8 + T cells in anti-GABA B receptor limbic encephalitis

Abstract: Objectives:To characterize the cellular autoimmune response in patients with γ-aminobutyric acid (GABA)B receptor antibody–associated limbic encephalitis (GABAB-R LE).Methods:Patients underwent MRI, extensive neuropsychological assessment, and multiparameter flow cytometry of peripheral blood and CSF.Results:We identified a series of 3 cases of nonparaneoplastic GABAB-R LE and one case of paraneoplastic GABAB-R LE associated with small cell lung cancer. All patients exhibited temporal lobe epilepsy, neuropsych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…20 In autoimmune encephalitis, much attention has been paid to analyses of antibodies, whereas T cell responses have rarely been studied. [21][22][23][24] We here found parallel intrathecal and parenchymal expansions of a likely pathogenic CD8+ T cell clone supporting the assumption that T cells have so far been unjustifiably disregarded. The link between the dominant role of autoantibodies and concomitant invasion of putatively pathogenic T cell clones requires further investigation in order to reveal the synergy between both arms of the adaptive immune system.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…20 In autoimmune encephalitis, much attention has been paid to analyses of antibodies, whereas T cell responses have rarely been studied. [21][22][23][24] We here found parallel intrathecal and parenchymal expansions of a likely pathogenic CD8+ T cell clone supporting the assumption that T cells have so far been unjustifiably disregarded. The link between the dominant role of autoantibodies and concomitant invasion of putatively pathogenic T cell clones requires further investigation in order to reveal the synergy between both arms of the adaptive immune system.…”
Section: Discussionsupporting
confidence: 80%
“…In autoimmune encephalitis, much attention has been paid to analyses of antibodies, whereas T cell responses have rarely been studied . We here found parallel intrathecal and parenchymal expansions of a likely pathogenic CD8+ T cell clone supporting the assumption that T cells have so far been unjustifiably disregarded.…”
Section: Discussionsupporting
confidence: 74%
“…It is a major finding of the present study that the quantitative RT-PCR data not only confirmed the delayed T-cell response, but was also able to demonstrate that the increase was attributable to an enhanced CD8 + T-cell population. While the pathophysiological role of CD8 + cells has already been suggested in the rodent kainate model [ 34 ], there is recent evidence on the pathogenic role of CD8 + cells in autoimmune anti-GABA-B-receptor encephalitis in humans [ 36 ], but intriguingly, also human temporal lobe epilepsy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there were no reports of investigations undertaken to explain the relationship between anti-GABA B -R encephalitis and AE with AS. Some research has suggested that T cell-based autoimmunity plays an important role in the development of anti-GABA B -R encephalitis [ 4 ]. Similarly, T cells were found to act in key pathogenetic roles in AS, as well [ 2 ].…”
Section: Discussionmentioning
confidence: 99%